Variations in village migration profiles in rural China： an analysis based on the second national agricultural census data - Wu, Bin; Robinson, Bernadette; Long, Wenjin (SAGE Publications, 2015)
Relatively little attention is paid to variations in rural migration at the village level even though labor supplying villages present considerable diversity in economic and development profiles. This paper examines the relationships between labor and household migration at the village level and the factors associated with different migration patterns through an analysis of data from China’s Second National Agricultural Census. The study identified four types of village migration profiles based on labor and household migration data from 4,482 villages in 10 counties across five provinces. Typical characteristics of each type villages are highlighted and implications for rural researchers and policy makers are discussed.